Pengaruh Penggunaan Media Game Edukatif terhadap Penguasaan Kosakata Anak Kelompok B di TK Islam Nurul Iman Sekarbela - Mudrika Lutfiah; Fahruddin; Muhammad Tahir; Abdul Kadir Jaelani (Mataram University, 2026)
Vocabulary mastery is one of the important aspects in early childhood language development that plays a role in children's communication skills and learning readiness. However, in learning practices, children are still found to have limited vocabulary due to the use of less varied and less interesting learning methods. Therefore, learning innovation is needed through the use of educational game-based digital media that can increase children's involvement in learning. This study aims to determine whether there is an effect of the use of educational game media on vocabulary mastery of group B children at Nurul Iman Sekarbela Islamic Kindergarten. This study uses a quantitative approach with an experimental method in the form of a Quasi Experiment, with a one group pretest -posttest design. Data collection techniques use observation and documentation using a validated observation sheet instrument, then the data analysis technique uses a normality test and hypothesis testing using a paired sample T-test with the help of SPSS (Statistical Product and Service Solutions) version 21. The population in this study were 164 early childhood children in group B at Nurul Iman Sekarbela Islamic Kindergarten. The sample in this study was 15 children in group B in group B1. The researcher used a sampling approach called purposive sampling (one group). Based on the results of the study, before the treatment, the average pretest score was 77.93. After the treatment, the average posttest score increased to 103.07. The hypothesis test shows that the significant value (2-tailed) is 0.001 with a sample size of 15 children at a 5% level. Based on the results of the 2-tailed sig. value obtained, namely 0.001, it can be said that 0.001 <0.05. Therefore, Ho is rejected and Ha is accepted, meaning that there is an influence of the use of educational games on the vocabulary mastery of group B children at Nurul Iman Sekarbela Islamic Kindergarten. Thus, it can be concluded that there is an influence of the use of educational game media on the vocabulary mastery of group B children at Nurul Iman Sekarbela Islamic Kindergarten.